TECHNICAL CONDITION OF IRRIGATION SYSTEMS OF TURKESTAN REGION AND THEIR IMPACT ON THE RECLAMATION STATE OF IRRIGATED ARABLE LAND (Journal of Geography and Environmental Management, 2026)
This article examines the current technical condition of irrigation systems in the Turkestan oblast and their impact on the meliorative status of irrigated agricultural lands. The study analyzes the degree of physical deterioration of the main irrigation and collector–drainage networks, the operational efficiency of hydraulic structures, as well as the influence of water delivery regimes on soil agromeliorative indicators. The information base of the research includes long-term archival materials, field observation data, and remote sensing data.The results of the study show that due to the unsatisfactory technical condition of irrigation and collection and drainage systems, about 10-15% of irrigated land in the Turkestan region is unused annually. In particular, 1.5–3% of irrigated areas are affected by severe salinization, 4–5.6% experience water shortages, 1.5–2% are subject to excessive groundwater level rise (above 2 m) or waterlogging, while 5.6–7% are not utilized due to the deterioration of irrigation systems and other financial and technical constraints.The findings demonstrate that the technical degradation of irrigation systems leads to intensified soil salinization and waterlogging processes, rising groundwater levels, and, consequently, a decline in the productivity of irrigated agricultural lands. The conclusions of the study provide a scientific basis for developing practical recommendations aimed at modernizing irrigation systems, improving water resource management, and enhancing the meliorative condition of irrigated lands in the oblast.
Keywords: irrigation systems; collector–drainage systems; soil salinization; Myrzashol irrigated massif; Kyzylkum irrigated massif